A Discussion About Two-Phase Flow Pressure Drop in Proton Exchange Membrane Fuel Cells. Issue 21 (29th November 2020) - Mortazavi, Mehdi; Heidari, Mahbod; Niknam, Seyed A.
Abstract: A proton exchange membrane (PEM) fuel cell produces water during its operation which results in a liquid-gas two-phase flow within its flow channels. Because the length scales associated with flow channels are small, the two-phase flow in PEM fuel cell is mainly dominated by capillary forces. These capillary forces tend to hold droplets within the channels which eventually increase the pressure drop along the flow channels. The two-phase flow pressure drop along the flow channel can reveal information about the amount of liquid water accumulation. Therefore, a precise two-phase flow pressure drop model that can accurately predict the pressure drop in PEM fuel cell flow channels can be beneficial in estimating the amount of water content in flow channels. In the current study, liquid-gas two-phase flow pressure drops were measured in an ex-situ test section with liquid water and air flowing within the range of PEM fuel cell flow conditions. The measured pressure drops were then compared with nine existing pressure drop models developed for minichannels. Qualitative and quantitative comparisons are provided to compare the prediction capability of the models. Also, a discussion about capillary-scale two-phase flow systems and suggestions to improve prospective two-phase flow pressure drop models is provided.